A Study of Relationship Between Total Productive Maintenance (TPM) and Manufacturing Performance - Nor Hafida, Hamzah (2011)
Most organizations production is based on machine – human system. The dependable of production system on machine has increased drastically with the increase of automation. The purpose of this study is to examine the relationship between Total Productive Maintenance (TPM) practices which are top management leadership, information system focus, employee involvement, and autonomous and planned maintenance with manufacturing performance. A total of 100 questionnaires were circulated to various manufacturing industries in Northern regions of Malaysia such as Kedah, Penang, and Perak. However, only 95 questionnaires were returned and usable for analysis. The correlation and multiple regression analysis were performed to test the hypotheses of the study. The findings indicated of the four (4) components of TPM, only employee involvement was not significantly related to manufacturing performance. This was aligned with the results shown in multiple regression analysis. In addition, the effectiveness of production is relying on skills level, management, and maintenance of equipment efficiently. The implications were discussed and recommendations for the future research were also addressed.